Design of Piezoelectric Energy Harvester Single Cantilever Beam for IoT applications and Micro-electronic devices - Ramizi Mohamed; Amna Riaz; Mahidur R. Sarker; José Luis Olazagoitia (Penerbit Universiti Kebangsaan Malaysia, 2025)
A few years back the power requirement of electronic devices was very high. But with the technological developments in the field of internet-based systems, the design of low-powered microelectronic devices, WSN and IoT devices became necessary. In these systems the size and the power requirement are low and in most situations the replacement of batteries is challenging. For these microelectronic and IoT devices the abundant energy harvester is very useful. Among different abundant energy resources, vibrational energy harvesting with piezoelectric cantilever beam energy harvesters is of interest. This research work presents the design and analysis of an energy harvester (EH) which contains a single piezoelectric cantilever beam that captures the vibrational energy of the suspension bridge. This approach ties the two things together by framing piezoelectric energy harvesting as a solution to the power challenges faced by low-powered devices, making the transition feel more natural and connected. The main challenge in the design was matching the resonance frequency of the bridge with a piezo EH which is around 2.5Hz to extract maximum power. To overcome this problem Eigen frequency analysis in COMSOL Multiphysics is done. The 3D geometry of single beam piezo EH is designed and analyzed in COMSOL Multiphysics solid works. In this research work a relationship is established between the geometrical parameters of the single beam piezo EH and Eigen frequency based on the first six Eigen frequency analyses in COMSOL Multiphysics. For fi nite element analysis (FEA) a piezo single beam harvester is vibrated by application of force which is equal to the vibrational force (0.98m/ s2) in the suspension bridge. The force of (0.98 m/s²) is chosen because it avoids resonating with critical system components. The output from the harvester is achieved at a resonance frequency of 2.5Hz. The output from the piezo is very low 800 milli volts at 2.5Hz. The output results of piezo EH are also compared with a cantilever beam with a single-branch structure.